Clinical implementetion of vildagliptin: data from recent studies comparing incretin-based medications - Elena Valer'evna Biryukova (Сахарный диабет)
The introduction of DPP-4 inhibitors substantially increased therapeutic options for type 2 diabetes mellitus (T2DM). The unique mechanism of action allows using these agents both as monotherapy and in combination with conventional anti-diabetes drugs. Evidence base for efficacy and safety of DPP-4 inhibitors deepens every year, but to date only a few studies addressed direct comparison between individual agents within this pharmacological class. Current article presents data from the studies comparing vildagliptin with other DPP-4 inhibitors, as well as GLP-1 agonists.